1975
DOI: 10.1177/23.5.1127223
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant density separation of cells. I. The buoyant distribution of guinea pig bone marrow cells.

Abstract: Guinea pig bone marrow cells were separated by buoyant density utilizing linear gradients of bovine serum albumin (BSA). It has finally become possible to characterize the cells present in the density fractions in terms of classical morphology. The development of the Cell Type computer program which calculates the percentages of the individual types of cells present in the fractions and their buoyant density distributions and plots the data has greatly facilitated and improved the accuracy of these studies. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…AchE is an enzyme which has been shown to be relatively specific for the megakaryocytic lineage in rodents, and can be identified in small cells which are unrecognizable as megakaryocytes by standard morphologic features (Jackson, 1973;Long and Henry, 1979;Long and Williams, 1981). Techniques for the separation and partial isolation of these classes of megakaryocytes have been described (Nakeff and Maat, 1974;Leif et al, 1975; 0 1985 ALAN R. LISS, INC Levine and Fedorko, 1976;Nakeff and Floeh, 1976;Pretlow and Stinson, 1976;Nachman et al, 1977;Sitar et al, 1977;Rabellino et al, 1979;Levine, 1980;Worthington and Nakeff, 1981;Williams et al, 1981;Long et al, 1982;Sitar, 1984). Rabellino et al (1979) found that mature human megakaryocytes are found at the top of discontinuous Percoll gradients at low density (less than 1.050 g/cm3).…”
mentioning
confidence: 99%
“…AchE is an enzyme which has been shown to be relatively specific for the megakaryocytic lineage in rodents, and can be identified in small cells which are unrecognizable as megakaryocytes by standard morphologic features (Jackson, 1973;Long and Henry, 1979;Long and Williams, 1981). Techniques for the separation and partial isolation of these classes of megakaryocytes have been described (Nakeff and Maat, 1974;Leif et al, 1975; 0 1985 ALAN R. LISS, INC Levine and Fedorko, 1976;Nakeff and Floeh, 1976;Pretlow and Stinson, 1976;Nachman et al, 1977;Sitar et al, 1977;Rabellino et al, 1979;Levine, 1980;Worthington and Nakeff, 1981;Williams et al, 1981;Long et al, 1982;Sitar, 1984). Rabellino et al (1979) found that mature human megakaryocytes are found at the top of discontinuous Percoll gradients at low density (less than 1.050 g/cm3).…”
mentioning
confidence: 99%